Study of the Antibacterial Activity of Artemisia Absinthium against E. coli bacteria Isolated from Urinary Tract Infections - Elham Jawad Kadhum (Recent Trends in Infectious Diseases, 2026)
Twenty clinically diagnosed samples were collected using transport medium swabs from the operating room at Al-Amal Specialized Laboratory in Iraq between November 2025 and February 10, 2026. Antibiotic susceptibility testing was performed on the 20 Escherichia coli samples. The results showed a clear difference in the bacterial isolates' response to the tested antibiotics. Imipenem demonstrated the highest inhibition rate, reaching 24.55% (100%), compared to the other antibiotics used in the study. This indicates the importance of this antibiotic in treating bacterial infections caused by these isolates. The results also showed that the antibiotic gentamicin exhibited good activity against the tested bacterial isolates, reaching 18.85 (90%), while moxifloxacin showed moderate activity (13.55), with varying responses among the isolates. Tetracycline showed limited activity (2.70, 80%), while all isolates were resistant to BY, which may reflect the prevalence of bacterial resistance mechanisms to this antibiotic due to its widespread use in treatment. The results presented in this study indicate that the hot water extract of Artemisia absinthium exhibited antibacterial activity that increased with increasing concentration. The 100% concentration recorded the highest inhibition zone diameter of 20 mm, indicating high efficacy in inhibiting bacterial growth. The 50% concentration recorded an inhibition zone diameter of 17 mm, indicating moderate antibacterial activity. The 25% concentration showed the least inhibitory activity with a diameter of 13 mm.
Keywords: Artemisia absinthium; Bacteria; E-Coli; Inhibition; moxifloxacin